Modelling the heat transfer process in selective laser melting - numerical and experimental study - Ong, Roger Rui Feng (2014)
Additive manufacturing (AM) is the process of creating three-dimensional (3D) solid objects of almost any shape from a digital model. It is also referred as 3D printing, and it works by adding layers of materials successively on top of each other, eventually forming parts of different shapes and sizes. It is different from conventional manufacturing methods, which operates by removing or forming materials from a bulk object.